2018
DOI: 10.1016/j.lcsi.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Connecting to the outside: Cultural resources teachers use when contextualizing instruction

Abstract: The aim of this article is to examine what resources teachers mobilize when contextualizing instruction. In this instructional method, teachers use students' everyday experiences as tools for teaching subject matter at school. Research has documented that contextualizing instruction can support classroom learning. However, we do not know very much about what types of resources teachers view as relevant in this type of instructional work. In this article, we analyze video data of student-teacher interaction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Still, as vignettes 2 and 3 demonstrate, it has the potential to be a promotional context for students' knowledge expansion and learning. The ways in which teachers interacted with students played a crucial role in mediating the students' opportunities to draw upon their funds of knowledge and productively connect this knowledge to their academic learning (see also Silseth, 2018;Silseth & Erstad, 2018). Our findings point to the need to research and better understand the role of the teacher in a FUSE studio and different makerspaces in general, identifying interaction processes among teachers and students that support and enhance students' knowledge creation processes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Still, as vignettes 2 and 3 demonstrate, it has the potential to be a promotional context for students' knowledge expansion and learning. The ways in which teachers interacted with students played a crucial role in mediating the students' opportunities to draw upon their funds of knowledge and productively connect this knowledge to their academic learning (see also Silseth, 2018;Silseth & Erstad, 2018). Our findings point to the need to research and better understand the role of the teacher in a FUSE studio and different makerspaces in general, identifying interaction processes among teachers and students that support and enhance students' knowledge creation processes.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies applying a funds of knowledge approach have largely focused on promoting inclusive educational practices for underrepresented students, with ethnography being conducted by teachers in students' homes and neighborhoods and within typical classroom settings (e.g., Barton & Tan, 2009;Moll, Amanti, Neff, & Gonzales, 1992;Vélez-Ibáñez & Greenberg, 1992). Recent research in regular classrooms has shown that the ways in which teachers interact with students play a crucial role in mediating students' opportunities to draw upon their funds of knowledge and productively connect this knowledge to academic learning (Silseth, 2018;Silseth & Erstad, 2018). Researchers have yet not examined how students' funds of knowledge are manifested in school-based technology-enhanced making and design environments.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In several of the research projects I have been leading we find that teachers struggle with creating learning environments that truly draw on informal learning experiences of students (Silseth & Erstad, 2018;Wiig, Silseth & Erstad, 2017). Teachers are generally positive to the importance of involving students' experiences and practices from other contexts as part of classroom activities but have problems to implement this in practice.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has attracted the interest of researchers in a number of fields, including game studies, education, and literacy studies. For example, Silseth and Erstad (2018) explored how teachers draw on students' leisure experiences to contextualize their classroom teaching, and Potter (2013) advises researchers to work with teachers and students to explore media-based learning at home, at school, and in in-between settings. In my own research, I have also observed the connections between learning at home and at school, and I will return to this issue later.…”
Section: Computer Games In Classroomsmentioning
confidence: 99%